The Influence of Learning Interest and Discipline on Academic Achievement: The Mediating Role of Motivation - Yohana Christina; Imaculata Fatima; Hyronimus Se (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the influence of learning interest and learning discipline on student learning outcomes, as well as to examine the role of learning motivation as a mediating variable at a public vocational high school in Indonesia. The main issue underlying this study is the low level of student motivation and discipline, as evidenced by passive attitudes, low self-confidence, and a lack of readiness to participate in learning. The method used was quantitative research with data collection via closed-ended questionnaires, observation, and report card documentation. The sample consisted of 128 students, selected using proportional random sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 4). The results of the study indicate that interest in learning and discipline in learning have a significant effect on learning outcomes, both directly and indirectly through learning motivation as a mediating variable. These findings support Vroom’s motivation theory and Bloom’s concept of learning outcomes, while also demonstrating that motivation serves as a crucial link between attitude, regulatory behavior, and academic achievement. The findings of this study emphasize that improving students’ interest and discipline in learning requires contextual learning experiences, in line with the principles of human resource development. Teachers serve as learning managers who employ performance management approaches to enhance students’ motivation, engagement, and learning behaviors.